Antifungal Activity and Biocontrol Potential of Simplicillium lamellicola JC-1 against Multiple Fungal Pathogens of Oilseed Rape - Wenting Li; Tao Luo; Juncheng Li; Jing Zhang; Mingde Wu; Long Yang; Guoqing Li (Journal of Fungi, 2022)
A fungal strain (JC-1) of Simplicillium was isolated from a pod of oilseed rape (Brassica napus) infested with the blackleg pathogen Leptosphaeria biglobosa. This study was done to clarify its taxonomic identity using morphological and molecular approaches, to characterize its antifungal activity through bioassays and genome-based identification of antifungal metabolites, and to determine its efficacy in inducing systemic resistance (ISR) in oilseed rape. The results showed that JC-1 belongs to Simplicillium lamellicola. It displayed a strong antagonistic relationship with L. biglobosa, Botrytis cinerea (gray mold) and Sclerotinia sclerotiorum (stem rot). The cultural filtrates of JC-1 showed a high efficacy in suppressing infection by S. sclerotiorum on detached leaves of oilseed rape. Genome analysis indicated that JC-1 has the capability of producing multiple antifungal metabolites, including aureobasidin A1, squalestatin S1 and verlamelin. Inoculation of JC-1 on seeds of oilseed rape caused a suppressive effect on infection by L. biglobosa on the cotyledons of the resulting seedlings, suggesting that JC-1 can trigger ISR. Endophytic growth, accumulation of anthocyanins, up-regulated expression of CHI (for chalcone isomerase) and PR1 (for pathogenesis-related protein 1), and down-regulated expression of NECD3 (for 9-cis-epoxycarotenoid dioxygenase) were detected to be associated with the ISR. This study provided new insights into the biocontrol potential and modes of action of S. lamellicola.